Enhancing efficiency of a renewable energy assisted system with adiabatic compressed-air energy storage by application of multiple Kalina recovery cycles. (May 2023) - Piri, Ali; Aghanajafi, Cyrus; Sohani, Ali
Abstract: As an effective solution for the increasing energy and environmental crises, application of renewable energy is growing worldwide at a rapid pace. Since the energy production by renewable energy resources changes during the time, energy storage technologies come into operation to regulate the output of such systems. This research work provides an innovative way to increase the efficiency of a renewable energy assisted system with the adiabatic compressed-air energy storage (A-CAES) by multiple Kalina recovery cycles, which have appropriate performance at the medium and low temperature levels. In the proposed system, three Kalina recovery cycles, two of which work in the charging phase and one of which works in discharging phase, are employed. A comprehensive thermodynamic analysis, including finding and comparing the sensitivity of different effective parameters on the system performance, is conducted. The results show that the power production of the system has been improved from 3776.7 kW to 3904.0 kW, which means 3.38 % increase. Moreover, the round-trip exergetic efficiency has increased by 3.12 %, i.e., from 41.7 % to 43.0 %. The corresponding value for the round-trip energy efficiency is also 3.30 %, where the values before and after optimization are 48.5 % and 50.1 %. Furthermore, the values of power production for the Kalina cycles I, II, and III (KCSI, KCSII, and KCSIII ) in the optimum condition are 69.3 kW, 79.7 kW, and 118.4 kW, respectively. The gained enhancement values have proven that the proposed system can enhance the system performance significantly. Highlights: A novel way to enhance the efficiency of a renewable assisted CAES is proposed. The proposed enhancement strategy utilizes multiple Kalina recovery cycles. 3.38 % increase in power production of the system is achieved. The round-trip energy efficiency reaches from 48.5 % to 50.1 %. There is 3.12 % enhancement in the round-trip efficiency of the second law.